American Political Development as a Process of Democratization - King, D; Lieberman, R (Johns Hopkins University Press, 2009)
“American Political Development as a Process of Democratization,” with Robert C Lieberman, in Democratization in America: A Comparative Historical Analysis, Eds. Desmond King et al. Baltimore: Johns Hopkins University Press, 2009.